2020
DOI: 10.1111/epi.16653
|View full text |Cite
|
Sign up to set email alerts
|

Reduced synaptic vesicle protein 2A binding in temporal lobe epilepsy: A [11C]UCB‐J positron emission tomography study

Abstract: In this positron emission tomography (PET) study with [ 11 C]UCB-J, we evaluated synaptic vesicle glycoprotein 2A (SV2A) binding, which is decreased in resected brain tissues from epilepsy patients, in subjects with temporal lobe epilepsy (TLE) and compared the regional binding pattern to [ 18 F]fluorodeoxyglucose (FDG) uptake. Methods: Twelve TLE subjects and 12 control subjects were examined. Regional [ 11 C]UCB-J binding potential (BP ND) values were estimated using the centrum semiovale as a reference regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 47 publications
4
56
0
1
Order By: Relevance
“…This approach may be of interest in studies of neurodegenerative and psychiatric disorders. Previously, we and others have reported differences in synaptic density as measured with 11 C-UCB-J PET in epilepsy, Alzheimer’s disease, PTSD, Parkinson’s disease and psychiatric disorders ( Chen et al, 2018 ; D’Souza et al, 2020 ; Finnema et al, 2020 , 2016 ; Holmes et al, 2019 ; Matuskey et al, 2020 ; Onwordi et al, 2020 ). As well, multi-modality approaches utilizing ICA have already been applied to find altered network integrity in dementing disorders ( Ripp et al, 2020 ).…”
Section: Discussionmentioning
confidence: 84%
“…This approach may be of interest in studies of neurodegenerative and psychiatric disorders. Previously, we and others have reported differences in synaptic density as measured with 11 C-UCB-J PET in epilepsy, Alzheimer’s disease, PTSD, Parkinson’s disease and psychiatric disorders ( Chen et al, 2018 ; D’Souza et al, 2020 ; Finnema et al, 2020 , 2016 ; Holmes et al, 2019 ; Matuskey et al, 2020 ; Onwordi et al, 2020 ). As well, multi-modality approaches utilizing ICA have already been applied to find altered network integrity in dementing disorders ( Ripp et al, 2020 ).…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, we have demonstrated a declined hippocampal synaptic density during chronic epilepsy, however, it was mainly restricted to the CA1 layer and not associated with seizure frequency. While such focal reduction might be difficult to detect in vivo given the spatial resolution of microPET cameras (range of 0.8–1.5 mm), the potential application of SV2A PET imaging as a non-invasive marker for epilepsy is supported by recent work demonstrating its applicability in rodents ( Bertoglio et al, 2019b , Thomsen et al, 2020 ), evidence of reduced synaptic density in KASE rats during the progression of epilepsy ( Serrano et al, 2020 ) and further corroborated by the observation that SV2A PET can detect the epileptogenic focus in patients with refractory TLE ( Finnema et al, 2016 , Finnema et al, 2020 ).…”
Section: Discussionmentioning
confidence: 79%
“…Although SV2A PET imaging is a recent development, it has already been used to study synaptic density in Alzheimer’s disease [ 32 ], depression [ 33 ], post-traumatic stress disorder (PTSD) [ 33 ], Parkinson’s disease (PD) [ 34 ], schizophrenia [ 35 ], and epilepsy [ 36 ]. Among other notable findings, one study found large reductions in synaptic density in the seizure onset zone (SOZ) relative to the contralateral side, providing a biomarker for accurately identifying the SOZ in the presurgical evaluation of these patients.…”
Section: Discussionmentioning
confidence: 99%